Examination timetabling for undergraduate programme using graph coloring approach / Norarida Abd Rhani ... [et al.] - Abd Rhani, Norarida; Mat Saad, Nor Najihah; Zulkfeli, Nabilah; Mazlan, Mardhiyah Marisha; Mahmud, Maziah; Mohamad, Siti Nurul Fitriah; Wan Yusoff, Wan Roslini (2021)
One of the most common academic scheduling issues that can be seen in any educational system is the generation of examination time tables. Traditionally, the system of managing a timetable was done manually by paper work and could create havoc if there were changes to be made. Nowadays with the advent of advanced computer softwares, it is feasible to develop a good quality timetable management system. Issues such as having a large number of students as well as courses offered could be tackled easily within a short period of time. Any clashes of timetabling that arise can be detected and remedied immediately. An algorithm based on Graph coloring technique is one of the feasible solutions that can address these issues of managing timetables. In this study, a systematic model was developed by using a graph coloring technique to generate an examination timetable based on the database obtained from the Examination Unit in UiTM Cawangan Kelantan, Machang Campus. In the problem domain, types of constraints are defined as hard and soft in order to accommodate certain decisions. Major part of solving is focused on the degree of constraint satisfaction. Workflow of the system is described by using a case study and efficient output was generated. The chromatic and clique numbers are also obtained in this paper.